A comparison of the acute effects of high intensity interval training and moderate intensity continuous training on working memory and emotional state in adolescent women with subthreshold depression - Yuan, Shiwei; Lin, Lili; Liu, Libin; Zhang, Xinyuan; Gu, Qian (Frontiers in Public Health, 2025)
ObjectiveVarious guidelines emphasize the cognitive and emotional benefits of physical activity. However, it is not yet clear what kind of exercise intensity is suitable for individuals with subthreshold depression. Therefore, this study aims to examine the effects of high intensity interval training (HIIT) and moderate intensity continuous training (MICT) on the working memory and emotional state.MethodsForty-nine female students with subthreshold depression (mean age 16.3 ± 0.5 yrs) completed 20-min group of sit (SIT), MICT, and HIIT on separate days in a counterbalanced order. The modified n-back task was employed to evaluate working memory. Emotional state was assessed using the Feeling Scale (FS) and Felt Arousal Scale (FAS).ResultsRegarding working memory, for accuracy, SIT (82.41 ± 13.79%), MICT (81.79 ± 13.19%) and HIIT (82.06 ± 11.36%) have no significant difference (all p > 0.05). However, for reaction time, MICT (459.86 ± 131.47 ms) is significantly faster than HIIT (491.16 ± 115.68 ms) (p = 0.046), and there is no significant difference between MICT and SIT (462.71 ± 120.64 ms) (p > 0.05). Concerning emotional state, for arousal, FAS scores significantly increased after both HIIT (2.39 ± 1.30 to 3.76 ± 1.12, p < 0.001) and MICT (2.55 ± 0.88 to 3.94 ± 1.08, p < 0.001) compared to pre-exercise, and the increase caused by them was significantly higher than that of SIT (HIIT: p = 0.011; MICT: p < 0.01). For pleasure, the increase in FS score after MICT (−0.27 ± 1.13 to 1.06 ± 1.79) was significantly higher than that of SIT (0.32 ± 1.38 to 0.58 ± 1.53) (p < 0.01).ConclusionAcute MICT can enhance working memory and improve the emotional state of adolescent women with subthreshold depression, while HIIT may decrease working memory and pleasure in this particular population.